2015
DOI: 10.4018/ijec.2015100104
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing in Business Meetings

Abstract: This article investigates users' perceptions of videoconferencing (VC) as a mode of communication in business meetings. The study demonstrates that affordance theory is a fruitful theoretical perspective for understanding what shapes users' perceptions of how well VC works as a communication technology in business meetings. The article is based on observation and qualitative interviews with VC users in a multinational company. The findings suggest that multiple factors affect user perceptions of VC, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The answer is that no one had to. Even though the capabilities and benefits of WCS were known before the crisis, the absence of necessity and prevailing social norms, such as the preference for face-to-face interactions (Larsen, 2015), prevented people from breaking their habit of meeting in person. The contact restrictions imposed to contain the spread of COVID-19 created the necessity that outweighed prevailing social norms.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The answer is that no one had to. Even though the capabilities and benefits of WCS were known before the crisis, the absence of necessity and prevailing social norms, such as the preference for face-to-face interactions (Larsen, 2015), prevented people from breaking their habit of meeting in person. The contact restrictions imposed to contain the spread of COVID-19 created the necessity that outweighed prevailing social norms.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
“…rather than "Hi, how are you?" In addition, while it approximates face-to-face interactions, WCS has to some extent continued to be perceived as a "second class" medium (Larsen, 2015), which created barriers to their widespread implementation and use.…”
Section: Introductionmentioning
confidence: 99%
“…This created a sense of seclusion, and as a result, Wei and Johnes (2005) concluded that web-based learning tools should complement traditional schooling and not replace it. Faceto-face meetings are still preferred for effective communication and successful mastery of knowledge and skills (Larsen, 2015).…”
Section: Favorable and Unfavorable Factors Affecting The Use Of Web Conferencing In Educationmentioning
confidence: 99%
“…Even though videoconferencing will never be as “rich” as in-person meetings, it is the communication channel which comes closest to personal meetings because of the many cues that are available. This leads to several advantages compared to other—less rich—ways of communicating: Turning on the webcam was found to increase creativity and perceived authenticity among the participants ( Olson et al, 2012 ) and participants experience a stronger connection and increased trust ( Larsen, 2015 ). Furthermore, attentiveness and engagement are higher in webcam-supported meetings, which in turn increase meeting effectiveness as soon as participants have become familiar with the technology ( Olson et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%